KEWENANGAN MENGUJI KONSTITUSIONALITAS PERATURAN DAERAH TERHADAP UUD 1945 - Permatasari, Indah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 4 (2015), 2015)
The local government is given authority by the constitution to establish local regulations. Problems are arise when there are local regulation that not compatible with the constitution. The next question that arises is who is authorized to examine local regulations that not compatible with the constitution. In contrary with those considerations, the substantial problems are formulated into two, regulations about examine local regulations with the constitution and  who is authorized to examine local regulations with the constitution. This legal research is normative legal research. This research used the statute approach and conceptual approach. Legal materials analysis techniques that are used in this research are description and interpretation techniques. There is no regulation about examine local regulations with the constitution. The way that can be done to examine local regulations with the constitution is lodge a judicial review to the Supreme Court and than lodge a constitutional review to the Constitutional Court. The other way to do is through a constitutional complaint, but this mechanism is not owned by the Constitutional Court. The establishment of examine local regulations with the constitution is important to provide legal certainty and the protection of constitutional rights to the citizens.
Keywords: Constitution; Constitutional Court; Local Regulations; Supreme Court